GE_GERICHTE P/4813/2016 vom 25. Mai 2018 - GE Cour de justice (2018)
CONTRAVENTION ; IN DUBIO PRO REO ; ERREUR SUR LES FAITS(DROIT PÉNAL) ; COURSE DE SERVICE ; URGENCE ; POLICE ; INDEMNITÉ(EN GÉNÉRAL) | LCR.90.al1; LCR.40; CCRA.29.al1; CCRA.16.al3; LOJ.129.al4; CPP.429.al1.leta